2014
DOI: 10.5665/sleep.3586
|View full text |Cite
|
Sign up to set email alerts
|

Motor Events during Healthy Sleep: A Quantitative Polysomnographic Study

Abstract: Quantification of motor phenomena is a basic prerequisite to develop normative values, and is a first step toward a more precise description of the various motor phenomena present during sleep. Because rates of motor events were unexpectedly high even in physiological sleep, the future use of normative values for both research and clinical routine is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 43 publications
5
84
1
3
Order By: Relevance
“…The patients we report had "any" EMG activity index values ranging from 13.7% to 37.6% utilizing the conventional 3-second mini-epoch scoring. Only patient 3 had an "any" EMG activity index that exceeded the cutoff for both RBD and the 95 th percentile of healthy normal reported by the SINBAR group and Frauscher et al 17,19 The nature of our report limits our ability to propose an "any" EMG activity index cutoff value for TSD. However, as the majority of our patients had normal values for their "any" EMG activity index, a normal index does not necessarily exclude TSD.…”
Section: Discussionmentioning
confidence: 46%
“…The patients we report had "any" EMG activity index values ranging from 13.7% to 37.6% utilizing the conventional 3-second mini-epoch scoring. Only patient 3 had an "any" EMG activity index that exceeded the cutoff for both RBD and the 95 th percentile of healthy normal reported by the SINBAR group and Frauscher et al 17,19 The nature of our report limits our ability to propose an "any" EMG activity index cutoff value for TSD. However, as the majority of our patients had normal values for their "any" EMG activity index, a normal index does not necessarily exclude TSD.…”
Section: Discussionmentioning
confidence: 46%
“…The fact that hypnic myoclonus displays the characteristics of fasciculation potentials has been noted also by Montagna et al (1988). A few studies have reported electrophysiologically confirmed benign fasciculation syndrome in the group of EFM patients (Frauscher et al, 2014;Raccagni et al, 2016).…”
Section: Neurophysiologymentioning
confidence: 89%
“…Frauscher et al (2014) reported non-excessive FM in every single subject in the group of 100 healthy subjects, whereas 9% met the criteria for the excessive form.…”
Section: )mentioning
confidence: 99%
“…All participating volunteers underwent a two-step screening process (telephone interview, personal investigation by a physician trained in sleep medicine) to exclude a relevant sleep, neurological, psychiatric or internal comorbidity as well as any use of central nervous system medication (for detailed methodology see [16]). …”
Section: Methodsmentioning
confidence: 99%